2001
DOI: 10.1590/s1413-86702001000500001
|View full text |Cite
|
Sign up to set email alerts
|

Cut and puncture accidents involving health care workers exposed to biological materials

Abstract: The first report of occupational acquisition of HIV appeared in 1984, and, by June, 1997, the Centers for Disease Control and Prevention (CDC) had reported 52 documented cases of seroconversion following occupational exposure to HIV-1 by health care workers of those cases. 47 (90.3%) were exposed to blood. The most frequent type of accident reported was percutaneous needlestick injury. Prospective studies have estimated that the risk of HIV transmission following percutaneous exposure to infected blood is 0.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
6
1
3
Order By: Relevance
“…In this study, 456 reported accidents with biological materials occurred and source-patient serology tested 21% positive for the HIV, HBV or HCV pathogens, thus increasing the risk of blood-borne pathogen transmission. This frequency was relatively higher when compared to that found by Kelen et al [22] and Lanphear et al [23], but lower than that found by Marino et al [24].…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, 456 reported accidents with biological materials occurred and source-patient serology tested 21% positive for the HIV, HBV or HCV pathogens, thus increasing the risk of blood-borne pathogen transmission. This frequency was relatively higher when compared to that found by Kelen et al [22] and Lanphear et al [23], but lower than that found by Marino et al [24].…”
Section: Discussioncontrasting
confidence: 61%
“…This type of accident, mainly with exposure to blood or bodily fluids should be treated as urgency, as the fastest the prophylaxis is initiated, the better the prognosis. 26 In our data we identified 47.88% of dental surgeons who reported accidents with potentially contaminated material. However, biological risk was overlooked in 74.15% of these incidents, since only 25.85% sought specialized medical assistance and of these, 42.10% were instructed to begin antiretroviral chemoprophylaxis and 5.26% received vaccination against hepatitis B.…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Lima et al, 32 an anesthetic needle (19.4%) and an exploratory probe Nº 5 (16.4%) were the most frequently mentioned instruments. Appropriate care of the injured and exposed area is essential, highlighting: do not squeeze or enlarge in any way the lesion and cleanse the injured skin 26 with soap and water (52.04%), chlorhexidine (15.84%) or antiseptic liquids such as povidone-iodine 10% PVPI (2.04%) or alcohol 70% (11.54%). The use of irritant solutions such as hypochlorite (10.18%) and hydrogen peroxide (8.37%), seen in our study, are not recommended as an antiseptic as they worsen the wound and facilitate infection.…”
Section: Discussionmentioning
confidence: 99%
“…The selective pressure of antibiotics and other medicines, as well as chemical compounds commonly discharged as healthcare residues, can lead to the proliferation of these pathogens [2]. These organisms, mainly bacteria, may show antimicrobial resistance and are potential contaminants for hospital surfaces and materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…As they are discharged with untreated residues, these microbial strains may contaminate both the hospital sewer systems and final disposal systems, such as sanitary landfills [3].…”
Section: Introductionmentioning
confidence: 99%